How do you solve using the completing the square method 0=x^2-3x-6?

1 Answer
Aug 14, 2017

x = 3/2 +- (33)^(1/2) / 2

Explanation:

We need to add a number to create the constant
(b/2)^2 which will make the perfect square ( x - (b/2))^2
Since b = - 3 then (b/2)^2 = 9/4
But we already have - 6 = - 24/4 so we need to add 33/4
And we also need to subtract 33/4 to keep the equation true
This results in
( x - (3/2))^2 = 33/4
Taking the root and adding 3/2 to both sides
gives the result
x = 3/2 +- (33)^(1/2) / 2